THE IMPORTANCE OF ISLAMIC RELIGIOUS EDUCATION AND MORAL EDUCATION IN BUILDING THE CHARACTER OF PRIMARY SCHOOL CHILDREN - Rodiyah, Muslimatur Rodiyah; Suhermanto, Suhemanto; Fawait, Agus (PROCEEDING OF INTERNATIONAL CONFERENCE ON EDUCATION, SOCIETY AND HUMANITY, 2023)
Religious education and Islamic morals have a very important role in shaping the religious character of elementary school (SD) children. This article examines the importance of religious education and Islamic morals as the main foundation in building religious character at an early age. Islamic religious education equips children with an understanding of religious values, introduces religious teachings, and forms a sense of obedience to God. Meanwhile, moral education helps children understand the difference between right and wrong, and develops good attitudes and empathy towards fellow humans and the environment. This article discusses various strategies and approaches that can be applied in integrating Islamic religious and moral education in the school environment. The role of teachers as role models and facilitators in helping children understand and apply religious and moral values is the main focus of this article. Apart from that, the importance of the role of parents and their cooperation in supporting religious character education at home and at school is also discussed in depth. The research method used in preparing this article is the literature study research method (Library Research) and includes qualitative research. By implementing effective Islamic religious and moral education, it is hoped that elementary school children can grow into individuals with strong religious character. They will be able to face situations and moral dilemmas with integrity and wisdom. Thus, this article emphasizes that religious education and Islamic morals in elementary schools have an important role in forming a young generation who are religious, have noble character, and are ready to become pillars of the nation who make positive contributions to society and the world